Turbulence in the near scrape-off layer towards the L-mode density limit in ASDEX-Upgrade. (October 2022) - Grenfell, G.; Manz, P.; Conway, G.D.; Eich, T.; Adamek, J.; Brida, D.; Komm, M.; Nishizawa, T.; Griener, M.; Tal, B.; Stroth, U.; ,
Abstract: The L-mode density limit in ASDEX Upgrade is investigated with focus on the scrape-off layer. We observe a chain of events that involves the collapse of the E × B outer shear layer (just outside the separatrix), widening of the electron pressure fall-off length, outer divertor detachment, density shoulder formation, reduction and flattening of the parallel Mach number, and enhanced turbulent cross-field transport. The latter effect was associated with higher amplitude density fluctuations at low frequencies, where the turbulent cross-phase between density and velocity fluctuations pointing radially outward was favourable.